The Ratification of Indonesia-Australia Comprehensive Economic Partnership Agreement: Investment Challenges and Opportunities - Pratama, Andistya; Yuliana, Ginna (Audito Comparative Law Journal (ACLJ), 2024)
This article aims to conduct a more in-depth study of Indonesia's challenges and opportunities after the ratification of the 2020 Indonesia-Australia Comprehensive Economic Partnership Agreement, hereinafter referred to as IA-CEPA. IA-CEPA offers opportunities for investment, trade in goods and services, and human resource capacity building for both countries. The Indonesian government needs to accelerate the harmonization of national laws related to the substance of IA-CEPA so that no legal conflicts harm Indonesia's national and economic interests. This research applied normative or doctrinal research methods, collecting legal materials with literature studies, which were then analysed with descriptive analysis techniques to find solutions to the problems raised. The results show that IA-CEPA brings great opportunities for economic growth in both countries. With greater access to each other's markets and cuts in trade tariffs, this agreement can stimulate greater trade and investment. IA-CEPA provides incentives for both countries to diversify their investment sources. This can help reduce dependence on one particular country or region and increase economic resilience.